2017
DOI: 10.3390/nu9060631
|View full text |Cite
|
Sign up to set email alerts
|

An Increased Dietary Supply of Medium-Chain Fatty Acids during Early Weaning in Rodents Prevents Excessive Fat Accumulation in Adulthood

Abstract: Medium-chain fatty acids (MCFA) are a directly and readily absorbed source of energy. Exposure early-in-life to increased MCFA levels might affect development and impact (lipid) metabolism later in life. We tested whether an increased MCFA intake early-in-life positively affects adult body composition and metabolic status when challenged by a western-style diet (WSD). Male offspring of C57Bl/6j mice and Wistar rats were fed a control diet (CTRL; 10 w% fat, 14% MCFA) or a medium-chain triglycerides (MCT) diet w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 53 publications
0
7
1
Order By: Relevance
“…The MCT diets used in this study were well tolerated by the DS mice and did not induce adverse effects. Whereas it was previously reported that MCT diets can influence body weight and fat mass, 30,31 we did not observe any differences from the control. This may be related to inclusion of proteins and carbohydrates to create a more balanced diet, along with the ability of the mice to adapt to the new metabolic conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…The MCT diets used in this study were well tolerated by the DS mice and did not induce adverse effects. Whereas it was previously reported that MCT diets can influence body weight and fat mass, 30,31 we did not observe any differences from the control. This may be related to inclusion of proteins and carbohydrates to create a more balanced diet, along with the ability of the mice to adapt to the new metabolic conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…In rats, high dietary intake of MCFA during pregnancy, prevented obesity in their offspring later in life (Dong et al, 2011). In a study of both rats and mice, increased early-in-life intake of MCFA protected against the negative effects of a high-energy diet in adulthood, such as fat accumulation and insulin sensitivity (Van de Heijning, Oosting, Kegler, & Van der Beek, 2017).…”
Section: Medium-chain Fatty Acids and Metabolic Responsesmentioning
confidence: 99%
“…Insulin sensitivity was assessed using GTT and ITT as previously described (21). Briefly, for the GTT assay, all rats were fasted overnight and administered glucose (2 g/kg) by intraperitoneal injection.…”
Section: Methodsmentioning
confidence: 99%